Usage of Presentation-PracticeProduction Method in Teaching English (Eurasian Research Bulletin, 2022)
This article provides information about a study that aims to use new method PPP during the lessons and provide opportunities for learners to use the target structure. Understanding of PPP method, advantages of PPP method and developing of this new method